2007
DOI: 10.1159/000100869
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Intramyocellular Lipid in Humans by in vivo <sup>1</sup>H-MR Spectroscopy

Abstract: Background: It is considered that the increasing intramyocellular lipid (IMCL) affects health risks and muscle attenuation. Though body fat increases significantly with age in lean humans, it is not known whether IMCL increases or not. In this study, we investigated the changes with age in IMCL concentrations in skeletal muscles using 1H-MR spectroscopy and studied them in relation to body fat percentage, waist-hip ratio, and blood components. Methods: Twenty-four lean young (age 21.2 ± 1.9, BMI 21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 42 publications
7
48
3
Order By: Relevance
“…Studies that improved insulin sensitivity by low-calorie diets in patients with T2D were accompanied by a reduction in IMTG content (Jazet et al 2008, Lara-Castro et al 2008. Insulin resistance associated with ageing (Nakagawa et al 2007), growth hormone administration (Krag et al 2007) and post-burn trauma (Cree & Wolfe 2008) has been reported to be associated with increased IMTG content. Current opinion is reasonably clear on the fact that IMTG is a useful marker of the level of cytosolic lipid accumulation, but it is more likely that active lipid metabolites such as LCACoAs, DAGs and ceramides or intermediates of FA oxidation pathways interfere with insulin action via a variety of potential mechanisms (Fig.…”
Section: Linking Intramyocellular Triglyceride Content and Insulin Acmentioning
confidence: 99%
“…Studies that improved insulin sensitivity by low-calorie diets in patients with T2D were accompanied by a reduction in IMTG content (Jazet et al 2008, Lara-Castro et al 2008. Insulin resistance associated with ageing (Nakagawa et al 2007), growth hormone administration (Krag et al 2007) and post-burn trauma (Cree & Wolfe 2008) has been reported to be associated with increased IMTG content. Current opinion is reasonably clear on the fact that IMTG is a useful marker of the level of cytosolic lipid accumulation, but it is more likely that active lipid metabolites such as LCACoAs, DAGs and ceramides or intermediates of FA oxidation pathways interfere with insulin action via a variety of potential mechanisms (Fig.…”
Section: Linking Intramyocellular Triglyceride Content and Insulin Acmentioning
confidence: 99%
“…However, it is important to realize that there are other abnormalities occurring in aged skeletal muscle. Other common phenotypical traits include, but are not limited to, increased intramuscular triglyceride (IMTG) accumulation, 55,56 insulin resistance, 57 and a reduced myofiber regenerative potential. 58 Although these factors were not measured in the present study, it is worth mentioning that several of the novel observations made in the present study may be relevant to these additional age-associated muscle alterations.…”
Section: Atrophy and Hypertrophy Signaling In Sarcopenia 171mentioning
confidence: 99%
“…16 Magnetic resonance images were acquired using a clinical 1.5-T whole-body scanner system (Signa Horizon LX, GE Medical Systems, Milwaukee, WI, USA), and a standard head coil (28 cm diameter) was used for detection. Transverse T 1 -weighed magnetic resonance images (echo time/repetition time¼8.5/400 ms) were acquired to determine the placement of the proton-MRS voxels.…”
Section: Imcl Content By Proton-mrsmentioning
confidence: 99%
“…IMCL and extramyocellular lipid were quantified relative to muscle water as described previously. 16 …”
Section: Imcl Content By Proton-mrsmentioning
confidence: 99%